1966
DOI: 10.1002/ijch.196600034
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Study of the Adsorption of Benzoic Acid and Nitrobenzene in Montmorillonite

Abstract: Nitrobenzene and benzoic acid are coordinated through water molecules to the more highly polarizing exchangeable cations in the Inte rlayer space of montmorillonite, but are directly coordinated to NH/ and possibly also K+: On dehydration of the adsorptlon complexes the nitrobenzene and benzoic acid become directly coordinated to all of the exchangeable cations investigated. Benzoate ion was also formed in amounts which were dependent on the exchangeable cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 18 publications
7
35
0
1
Order By: Relevance
“…The NO2 in plane symmetric deformation at about 850 cm a is lower and broader compared to the corresponding band of the unadsorbed compound. Similar results were obtained with nitrobenzene and parathion adsorbed on montmorillonite (Saltzman and Yariv, 1976;Yariv et al, 1966). According to Nakamoto (1978), the shift of both NO2-stretching bands to lower frequencies indicates that the nitro group's two oxygens are involved in the coordination bond.…”
Section: Resultssupporting
confidence: 79%
“…The NO2 in plane symmetric deformation at about 850 cm a is lower and broader compared to the corresponding band of the unadsorbed compound. Similar results were obtained with nitrobenzene and parathion adsorbed on montmorillonite (Saltzman and Yariv, 1976;Yariv et al, 1966). According to Nakamoto (1978), the shift of both NO2-stretching bands to lower frequencies indicates that the nitro group's two oxygens are involved in the coordination bond.…”
Section: Resultssupporting
confidence: 79%
“…It is suggested that in the 14.7 A Mg and Ca complexes the higher frequency band, at 1233 and 1248 cm -a respectively, arises from the v(NO) of PNO water bridged to the cation as these are in the region of the v(NO) frequency (1235 cm -~) in the 21 A complexes ( Table 2). The lower frequency bands, at 1222 and 1214cm -1 respectively, are interpreted as being due to PNO directly coordinated to the cation, in keeping with similar observations on other complexes (Farmer and Mortland, 1966;Yariv et al, 1966;Parfitt and Mortland, 1968). The absence of a 8(OH) band at 1622 cm -1 in the spectrum of the Mg complex (see Figs.…”
Section: Ir Spectrasupporting
confidence: 87%
“…Pyridine gave spacings of 14.7 and 23 A; the 14-7 fi spacing also corresponded to a monolayer, but with an almost perpendicular orientation of the pyridine ring to the clay surface. Nitrobenzene and benzoic acid also gave spacings around 15-2 as well as 12.4-12.8 and 15.1 A respectively (Yariv, Russell and Farmer, 1966) which correspond to one of the above orientations for the molecule. The fiat orientation of the pyridine ring may thus be an unfavourable one for PNO in montmorillonite, since spatial considerations could keep the coordination requirements of PNO around the cation from being fulfilled.…”
Section: X-ray Diffractionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some AMT molecules may have displaced water to become directly coordinated with the cation, as a consequence of the high polarizing strength of the Mg 2 § cation. This behaviour has previously been observed in benzonitrile-montmorillonite complexes (Serratosa, 1968), nitrobenzene-montmorillonite complexes (Yariv et al, 1966), and also in AMTmontmorillonite complexes (Morillo et aL, 1991) when the solution pH was 6.3 and conditions were different from those used in the present study. In both cases, AMT as a cation and as a dipole contains the exocyclic group C=NH e+ (Fig.l, II) which is responsible for the 1690 cm -1 band.…”
Section: And Discussionsupporting
confidence: 87%